Localized hypertrichosis at unusual sites - Anshul Maheshwari; Daulat Ram Dhaked; Ram Singh Meena (Wolters Kluwer Medknow Publications, 2017)
Localized hypertrichosis is a rare entity characterized by circumscribed patches of terminal hair. It may be associated with many underlying systemic abnormalities. In our case, a 5-year-old girl presented with complaints of multiple patches of hypertrichosis without any systemic abnormality since the last 4 years. We are reporting this case due to the rarity of hypertrichosis at abnormal sites.